Relaciones entre estilos de personalidad y tipos de consumo de alcohol (2013)
ABSTRACT: To detect the rate of alcohol consumption and its relation to personality styles in the adult population of the town of “El Retiro” (Antioquia, Colombia). Method. The study was cross-sectional, descriptive and correlational. Two instruments were applied, the Millon Inventory of Personality (MIPS) and Alcohol Use Disorder Identification Test (Audit) in a sample of 61 participants, of which 33 were men and 28 were women. Results. The most common rate of drinking in El Retiro was Safe Consumption (68.9%). There were statistically significant differences in the rate of alcohol consumption by gender, with men in particular showing alcohol dependence. In the case of men, alcohol consumption is related to personality styles such as Innovation (r = 0.35) Discrepancy (r = 0.40), and Domain (r = 0.46) and in women Discrepancy (r = 0.38), Expansion (r = 0.39), Modification (r = 0.40) and Adequacy (r = 0.42). Consumption of risk for both genders correlated to the style of systematization (r = 0.67), harmful use with protection (r = 0.89) and alcohol dependence with indecision (r =0.99). Conclusion. The three main categories which group the personality styles of motivational goals, cognitive modes and interpersonal behaviors are differentially associated with consumption without risk, with risk, harmful and dependent, with significant gender-related differences when taking into account personality style and consumption.